Quantification of microporosity and its effect on permeability and acoustic velocity in Miocene carbonates, Central Luconia, offshore Sarawak, Malaysia - Janjuhah, H.T. (2019)
Carbonate reservoirs are mostly considered to be complicated since in the petroleum industry, and because predicting the quality and achieving a high recovery factor from these rocks is challenging. Carbonate rocks have a complex porosity, which often leads to substantial uncertainty in prediction of permeability values for any particular porosity figure. The petrophysical analysis of carbonate reservoirs is and prone to more significant uncertainty. Pore size in carbonates rocks varies from micro to cave system scale. Carbonates with moldic and vuggy porosity usually contribute positively to the hydrocarbon production, yet sometimes these pores are mostly unconnected, thus yielding low flow rates, even though micropores form a high component of the total porosity of a reservoir. This study explores the reservoir properties of carbonate rocks of Central Luconia (Offshore Sarawak, eastern Malaysia), with emphasis on the relevance of microporosity on permeability and acoustic velocity relationships. A petrographic study of 260 samples obtained from the reservoir interval of Well A in the Central Luconia, Malaysia, was conducted to identify pore types (moldic, vuggy, interparticle, intraparticle and fractures) and measure porosity (ranging from 4 to 25). For microporosity quantification, an enhanced workflow is introduced using the Digital Image Analysis (DIA) technique, where 32 petrographic images of each thin sections were taken under the transmitted light microscope that covers the entire thin section. The DIA technique was then implemented on these petrographic images to quantify the amount of macroporosity. After that, the microporosity was calculated in the following way: the difference in value between the observed macroporosity using DIA, and the total porosity measured on core plugs. Finally, the resulting amount of microporosity was then correlated with acoustic velocity and permeability to determine if significant improvement is achieved in the coefficient of determination (R2). Moreover, it has increased from 0.55 to 0.67 for the permeability and from 0.61 to 0.87 for the acoustic velocity. The analysis also highlights that those samples with more substantial pores and a high figure (>50 of total porosity) of microporosity exhibit slower acoustic velocity for both P and S waves. Also, this study proposed a simple predictive model of elastic properties in the Central Luconian Miocene carbonate, Malaysia. Â© 2018 Elsevier B.V.